Enhancing Students’ Speaking Skills through the Jigsaw Method: A Collaborative Learning Approach - Nuralam Jumadi; Sam Hermansyah; Buhari; Sitti Aisa (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This research aims to enhance students’ speaking skills through the implementation of the Jigsaw Method as a collaborative learning approach. The subjects of the study were students of class VIII.2 at UPT SMPN 4 Panca Rijang, selected through purposive sampling due to their low speaking skill. The study employed a pre-experimental design using a one-group pretest-posttest model. The instruments used were speaking tests and questionnaires. Data were analyzed quantitatively using a paired sample t-test with SPSS 25. The results showed a significant improvement in students’ speaking scores, with the mean increasing from 53.22 in the pretest to 73.65 in the posttest. The t-test revealed a significance value of 0.000 < 0.05, indicating a statistically significant difference. Moreover, questionnaire responses showed that most students had positive perceptions of the Jigsaw Method. They felt more confident, active, and engaged in speaking activities through group collaboration. The Jigsaw Method is proven to be effective in improving students’ speaking abilities while fostering peer interaction and responsibility in the learning process. It is recommended as an alternative strategy for teaching speaking skills in junior high school English classes.